A Shift in Corporate Social Responsibility Program to Support Vocational Education in Indonesia - Mgs Ahmad Ramadhani; Ety Rahayu (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The high unemployment rate in Indonesia can be alleviated through Corporate Social Responsibility (CSR) program in the education sector. This paper is aimed to examine how could that figure derived from vocational school graduates be reduced by the program in education that taking an opportunity from current several regulations issued by central government and competency-based human resources development to equip students and graduates with a set of competencies hence they will be competent and able to compete in the job market. This article was produced by using a systematic literature review method to explore and provide an overview of CSR program shifting in the education setting. The authors recommended the switch from a traditional or philanthropic model to a contemporary or strategic one by deploying internship, apprenticeship, and teaching factory to surmount the aforementioned issue. Finally, this paper offers managerial implication in general and suggestion for future academic research to explore and to assess their effectiveness in tackling poverty and impact on corporations, schools, and students or graduates.